Potential Bioactive Compounds of Mahogany Seeds (Swietenia mahagoni Jacq.) as Antidiabetics through Computational Studies in Silico Molecular Docking - Humaedi, Aji; Ardiansyah, Muhamad; Widianti, Audrey Agustin; Sharqoni, Muh Aly (Jurnal Mandala Pharmacon Indonesia, 2025)
Diabetes is a chronic endocrine metabolic disorder in insulin production or insulin resistance. Mahogany seeds are plants that have bioactive compounds that can treat diabetes mellitus. This study was conducted to determine the interaction between bioactive compounds of mahogany seeds and the Protein Tyrosine Phosphatase-1B (PTP1B) receptor with PDB ID code: 1T49. Bioactive compounds from mahogany seeds were subjected to docking simulations of 15 compounds with the reference ligand glibenclamide. In silico studies showed an interaction between bioactive compounds of mahogany seeds and PTP1B, the results obtained were in the form of binding energy between the ligand and the target protein. The compound with the best binding energy value was MSC15 (Chisocheton) with a binding energy value of -8.86 kcal/mol. The PyMOL program was used to visualize the 3D conformation of the molecule and ligand-protein interactions, the output was in the form of a Root Mean Square Deviation (RMSD) value of 1,363 Å show good value. The mahogany seed test ligand was also tested pharmacokinetically using the website https://preadmet.bmdrc.kr/  ,Pharmacokinetic parameter tests showed that mahogany seed compounds have excellent intestinal absorption (HIA >90%), strong plasma protein binding (>80%), and variable clearance rates, indicating high potential as an antidiabetic candidate.